2019
DOI: 10.5430/afr.v8n1p118
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ Remuneration and Corporate Social Responsibility: A Study on Malaysian Listed Firms

Abstract: The main objective of this paper is to examine the relationship between directors' remuneration and Corporate Social Responsibility (CSR) for listed firms in Malaysia. All financial data such as firm size, performance and leverage can be collected from Thomson Reuters DataStream while directors' remuneration and CSR disclosures were collected from annual reports. 377 samples of listed firms on Bursa Malaysia were collected from year 2014 to 2016. The results of this study show that increase director' remunerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Our result supports the agency theory assumption, which emphasises the role of the non-executive directors in improving management monitoring, indicating that investing in highly qualified external directors would bring better monitoring of executive directors' actions, hence improving disclosure practices. These results are in line with those of previous studies that found a positive relationship [68,88]. The results are also in line with the findings reported by [85], who documented a positive relationship between NEDREM and financial reporting quality in Malaysia (proxied by earnings management).…”
Section: The Relationship Between Board Characteristics and Ir Practicesupporting
confidence: 93%
See 1 more Smart Citation
“…Our result supports the agency theory assumption, which emphasises the role of the non-executive directors in improving management monitoring, indicating that investing in highly qualified external directors would bring better monitoring of executive directors' actions, hence improving disclosure practices. These results are in line with those of previous studies that found a positive relationship [68,88]. The results are also in line with the findings reported by [85], who documented a positive relationship between NEDREM and financial reporting quality in Malaysia (proxied by earnings management).…”
Section: The Relationship Between Board Characteristics and Ir Practicesupporting
confidence: 93%
“…Some empirical research examining the effect of board remuneration on non-financial disclosure provides mixed results. Some studies have shown that director remuneration is positively correlated with the voluntary disclosure level [87], environmental performance [67], CSR reporting [88] and sustainability disclosure [68]. This is because the board's remuneration is an indicator of a powerful monitoring tool.…”
Section: Board Remuneration and Ir Practicementioning
confidence: 99%
“…Hasil tersebut dikarenakan remunerasi dewan direksi dapat menyelaraskan kepentingan pemegang saham dan manajer untuk bekerja keras agar dapat berkurangnya biaya agensi, meningkatkan arus kas dan penilaian perusahaan. Hasil penelitian ini mendukung hasil penelitian (Haque (2017), Hu & Loh (2018), Maas & Rosendaal (2016), Mohd Razali et al (2019, Premavari & Utami (2020) dan Velte (2016)). Penelitian Hartikainen et al (2021) berpendapat berbeda dengan penelitian lainnya yang membuktikan bahwa variabel remunerasi dewan direksi tidak signifikan terhadap indeks laporan keberlanjutan.…”
Section: ______unclassified
“…Hubbard et al (2017) in their study also proves that investment in CSR practices in the past results in better financial performance thereby boosting the CEO's career and therefore resulting in more compensation. The increase in remuneration motivates the directors of the firm to perform more CSR practices which ultimately results in enhanced shareholder's value (Razali et al, 2019).…”
Section: Introductionmentioning
confidence: 99%